2009
DOI: 10.1159/000196812
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol versus Haloperidol plus Ondansetron for the Prophylaxis of Postoperative Nausea and Vomiting after Ophthalmologic Surgery

Abstract: Introduction: In this prospective, randomized, and double-blinded study we investigated the efficacy of haloperidol (10 μg/kg) and the combination of haloperidol (10 μg/kg) with ondansetron (0.1 mg/kg) for the prophylaxis of postoperative nausea and vomiting (PONV) after ophthalmologic surgery. Methods: 60 patients (ASA status 1–3) with risk factors for PONV (female, non-smoker, motion sickness or PONV in history, opioids for postoperative analgesia) undergoing retinal or strabismus surgery were included into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
1
9
0
2
Order By: Relevance
“…In the O&Hal1 group, 42% (CI: 32-53) of patients suffered from EE vs 20% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), 25% (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 30% in groups O&Dex, O&Hal2 and O&Dro respectively (P=.005). These significant differences were observed in groups O&Dex and O&Hal1 from the 6 to 12 h interval ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the O&Hal1 group, 42% (CI: 32-53) of patients suffered from EE vs 20% (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), 25% (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 30% in groups O&Dex, O&Hal2 and O&Dro respectively (P=.005). These significant differences were observed in groups O&Dex and O&Hal1 from the 6 to 12 h interval ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29][30] Various studies using haloperidol 1 mg have shown that it is effective 15,28,31,32 but other studies have not achieved the same results. 33,34 Even so, clinical guidelines recommend the use of haloperidol 1 or 2 mg in combination. 8,27,35,36 In the studies that showed haloperidol to be effective, patients were either not high-risk or were not observed for a sufficient length of time.…”
Section: Discussionmentioning
confidence: 99%
“…La combinación de 2 medicamentos antieméticos es efectiva en la profilaxis de náusea y vómito postoperatorio (evidencia categoría A2-B), sin diferencias en los efectos secundarios como cefalea, mareo, somnolencia e inquietud 24,31,32,48,53,56,[68][69][70][71][72][73][74][75][76][77] .…”
Section: Combinacionesunclassified
“…В ряде исследований доказано наличие противорвотной активности галоперидола, эффективность которого сопоставима с ондансетроном и особенно высока в их комбинации [41]. Недо статком является кратковременность действия -3 часа [1].…”
Section: современное состояние проблемы профилактики потрunclassified